Protocol for a pragmatic cluster randomised controlled trial for reducing irrational antibiotic prescribing among children with upper respiratory infections in rural China. Issue 5 (27th May 2016) - Zou, Guanyang; Wei, Xiaolin; Hicks, Joseph P; Hu, Yanhong; Walley, John; Zeng, Jun; Elsey, Helen; King, Rebecca; Zhang, Zhitong; Deng, Simin; Huang, Yuanyuan; Blacklock, Claire; et al.
Abstract : Introduction: Irrational use of antibiotics is a serious issue within China and internationally. In 2012, the Chinese Ministry of Health issued a regulation for antibiotic prescriptions limiting them to <20% of all prescriptions for outpatients, but no operational details have been issued regarding policy implementation. This study aims to test the effectiveness of a multidimensional intervention designed to reduce the use of antibiotics among children (aged 2–14 years old) with acute upper respiratory infections in rural primary care settings in China, through changing doctors' prescribing behaviours and educating parents/caregivers. Methods and analysis: This is a pragmatic, parallel-group, controlled, cluster-randomised superiority trial, with blinded evaluation of outcomes and data analysis, and un-blinded treatment. From two counties in Guangxi Province, 12 township hospitals will be randomised to the intervention arm and 13 to the control arm. In the control arm, the management of antibiotics prescriptions will continue through usual care via clinical consultations. In the intervention arm, a provider and patient/caregiver focused intervention will be embedded within routine primary care practice. The provider intervention includes operational guidelines, systematic training, peer review of antibiotic prescribing and provision of health education to patient caregivers. We will also provide printed educational materials and educational videos to patients' caregivers. The primary outcome is the proportion of all prescriptions issued by providers for upper respiratory infections in children aged 2–14 years old, which include at least one antibiotic. Ethics and dissemination: The trial has received ethical approval from the Ethics Committee of Guangxi Provincial Centre for Disease Control and Prevention, China. The results will be disseminated through workshops, policy briefs, peer-reviewed publications, local and international conferences. Trial registration number: ISRCTN14340536; Pre-results.